Cleidocranial Dysplasia Causing Respiratory Distress in Neonates: A Case Report and Literature Review - Xue, Ru; Zhang, Guoqing; Chen, Xiafang; Ye, Xiuxia (Frontiers in Genetics, 2021)
Cleidocranial dysplasia (CCD; OMIM 119600) is a rare autosomal dominant skeletal dysplasia, which is mainly characterized by persistently open or delayed closure of fontanelle, patent skull sutures, abnormal clavicles, pectus excavatum, short stature, supernumerary teeth, and sinus and middle ear infections. It is caused by Runt-related transcription factor 2 (RUNX2;OMIM 600211) mutations. Herein, we presented a rare case of CCD with neonatal respiratory distress, who had abnormal midfacial features and wide fontanelle. And pectus excavatum was noted. He was transferred to our department, administered standard medical treatment, and discharged after four weeks. Therefore, we recommend the early suspicion and identification of this rare inherited disease to adequate treatment.